Low-temperature synthesis of cds and zns nanoparticles by solution method using an anionic surfactant - Carrillo, Amanda (2018)
In this work, we present a novel and simple solution method to synthesize cadmium sulfide (CdS) and zinc sulfide (ZnS) nanoparticles (Nps). The solution-based processes for CdS and ZnS were carried out at room temperature (27 °C) using sodium dodecyl sulfate (SDS) as anionic surfactant for both chalcogenide systems. Thioacetamide (C2H5NS) was used as anionic precursor, and as the metal precursor cadmium chloride (CdCl2) and zinc acetate (C4H6O4Zn. 2H2O) for CdS and ZnS Nps respectively. The pH for the solution of nanoparticles was 2.2 for CdS and 5.7 for ZnS. The conductivity for chalcogenide solution was also determinate. Optical properties of CdS and ZnS nanoparticles were analyzed by Ultraviolet-Visible (UV-Vis) spectroscopy; functional groups were identified by Fourier transform infrared spectroscopy (FTIR), the surface morphology by scanning electron microscopy (SEM) and the crystalline structure by X-Ray diffraction (XRD). The distribution size for nanoparticles were less than 100 nm for CdS and ZnS Nps.